Gut Microbiota Is Involved in Alcohol-Induced Osteoporosis in Young and Old Rats Through Immune Regulation - Cheng, Ming; Tan, Bo; Wu, Xiaojing; Liao, Feng; Wang, Fei; Huang, Zuoyao (Frontiers in Cellular and Infection Microbiology, 2021)
Long-term chronic and excessive alcohol consumption are risk factors for osteoporosis. Excessive drinking can reduce bone density and also cause imbalance of gut microbiota. And gut microbiota can affect bone metabolism through various mechanisms, and the regulation of gut microbiota is closely related to age. However, the effects of gut microbiota on alcohol-induced osteoporosis at different ages is unclear. In this study, young and old rats were used to induce osteoporosis by long-term chronic alcohol consumption, and the alcohol metabolism, bone morphology, bone absorption and immune activity of rats were analyzed to determine the effects of alcohol on rats of different ages. In addition, changes of gut microbiota in rats were analyzed to explore the role of gut microbiota in alcohol-induced osteoporosis in rats of different ages. The results showed the ability of alcohol metabolism was only associated with age, but not with alcohol consumption. Long-term alcohol consumption resulted in the changes of bone metabolism regulating hormones, bone loss, activation of receptor activator of NF-κB ligand (RANKL) signaling and inflammatory response. And osteoporosis was more severe in old rats than young rats, suggesting that alcohol-induced osteoporosis is age-related. In addition, long-term drinking also affected the composition of gut microbiota in rats, with a significant increase in the proportion of pro-inflammatory microorganisms. Overall, this study found that long-term alcohol consumption induced osteoporosis and affected the composition of gut microbiota. The changes of gut microbiota might activate T lymphocytes, produce cytokines, and then activate osteoclasts. In addition, the osteoporosis was more severe in the old rats than young rats, which may be due to the higher diversity and stronger regulation ability of gut microbiota in young rats compared with old rats.